Envejecimiento y Universidad de Chile - Castillo S., Manuel Domingo (Revista Hospital Clínico Universidad de Chile, 2008)
There is a possibility and opportunity so that the university takes the thematic one of the Aging like a great strategic priority, through a reciprocal flow, a dialogue between this one and the society, where each part contributes, it offers and it demands what needs. From the condition of doctor I can contribute with programs of education for the health in the old one, or when own developing our cautious one about the “Successful Aging “, but as architect in the forms to construct and to design the dwelling or the habitat of the old ones, like lawyer through progress of the legislation towards the senectud, like philosopher teaching and sharing the visions of the world and the spirit, the place of the Ethics in the society. Own the literato or the engineer or social worker. A universe that emanates and flows from the University towards the old one which he is alive and concrete socially. The university is enough more than its building and foundations, are immersed, concur, belong to the essence, can contribute to the best aging of the population. By its history and east relevance space and this opportunity can be filled by the University of Chile.